Aplicação do Processo Hierárquico Analítico (AHP) para o Mapeamento de Suscetibilidade ao Voçorocamento no município de Capão do Cipó – RS/Brasil - Antônio Von Ende Dotto; Marinéli Moraes Gaberti; Luís Eduardo de Souza Robaina (Confins)
Erosion has been highlighted in scientific works due to growing concerns about the loss of arable land, soil degradation and silting up of river channels. The present work presents the Mapping of Susceptibility to gullies in the municipality of Capão do Cipó from multicriteria analysis with the Analytical Hierarchical Process (AHP) technique and support of geotechnologies. Through the automated crossing of regulators (slope shapes, soils, lithology, land use and land cover), a cartographic product divided into five classes was developed: Very Low, Low, Medium, High and Very High. Validation was carried out through the identification of existing erosion processes through images and field work. The map resulting from the spatial information was satisfactory, as most of the identified gullies are located in areas with high susceptibility, consistent with the reality of the municipality. The methodology presented is satisfactory and can be replicated in other areas with similar characteristics. The resulting products can serve as a subsidy both for scientific purposes and for territorial management for the control and recovery of degraded areas or for monitoring the possible start of the gullying process.